2004
DOI: 10.1093/brain/awh191
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MRI of brain inflammation in human ischaemic stroke

Abstract: Inflammation contributes to brain damage caused by ischaemic stroke. Macrophages, as the prevailing inflammatory cell population in stroke lesions, can be visualized using ultrasmall superparamagnetic iron oxide (USPIO) as a cell-specific contrast agent for MRI. In this single-centre open-labelled clinical phase II study we tested the potential of USPIO-enhanced MRI for macrophage imaging in human ischaemic stroke lesions. In a series of 10 consecutive patients, USPIO contrast agent was infused at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(156 citation statements)
references
References 24 publications
8
146
1
Order By: Relevance
“…Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence. Brownian forces also prevent the aggregation of the SPIO due to magnetic attraction in solution.…”
Section: Magnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence. Brownian forces also prevent the aggregation of the SPIO due to magnetic attraction in solution.…”
Section: Magnetismmentioning
confidence: 99%
“…90 Typically, in vivo, smaller nanoparticles (15-30 nm hydrodynamic diameter) with longer circulation times exhibit improved contrast at sites of inflammation compared with larger nanoparticles. 53 The role of macrophages in pathologic tissue alterations in the central nervous system (CNS) has also provided the opportunity for the use of SPIO agents for the imaging of strokes 127 (Fig. 3), multiple sclerosis, 33 brain tumors, 2,37 and carotid atherosclerotic plaques.…”
Section: Macrophage Imagingmentioning
confidence: 99%
“…The suitability of SPIO for MRI of the CNS was able to be shown in neurovascular (infarction [88]), neuro-oncological (tumors [89]) or neuroinflammatory processes (multiple sclerosis (MS) [90]) as well as for angiography and perfusion diagnosis [91]. Increased accumulation of SPIO in the microglia of the CNS in the case of disruption of the blood brain barrier (BBB) in tumorous CNS lesions [89] or inflammatory CNS lesions [92] which can be imaged with the help of T2w/T2*w MR sequences is observed in the case of the former applications.…”
Section: Cns Imagingmentioning
confidence: 99%
“…Saleh et al 46 performed the first clinical MRI study of ischemic stroke in 10 patients comparing Gd and USPIO contrast agents. Corresponding to the defined time delay of macrophage CNS infiltration in experimental studies, MRI scans were performed 4 to 6 days after stroke onset.…”
Section: Cerebral Ischemiamentioning
confidence: 99%